Incidencia de la punta morada en el cultivo de tomate de árbol (Solanum Betaceum) en la terraza de banco en el Campus Salache, Latacunga, Cotopaxi 2022. - Faz Guzmán, Kevin Tomás (2023)
The purple tip is known by the damage that it means for the crops of tree tomato, for this reason, the present investigation has as objective to determine its incidence and affection to these sowings, by means of the observation of infected plants of tree tomato it is possible to register a precedent in the control of the plagues Phytosanitary and diseases; through the observation to the terrace of the bank number eight same that is in the Technical University of Cotopaxi to an altitude of 2747 m. s.n.m. with 78° 37'27'' west longitude and 0° 59' 59'' south latitude, which was taken as a sample for the investigation due to the type of pest that was found in the tomato crop (Solanum betaceum Cav) of the terrace. Bactericera cockerelli or also called purple tip observed in the leaves of the tomato plant of tree disappears in cold seasons since they are insects of warm climate, which go through three stages of formation which are: egg, nymph and adult, with a fast reproduction, from 22 to 45 days they pass from the stage of egg to adult and have the capacity to lay from 500 to 1. The insects by their nature do not remain in a single plant but fly from one place to another in the crop, which makes it difficult to keep an exact record of their permanence and affection to each plant, however, the research process during five continuous months has allowed to determine the process of deterioration of the plant infected by this pest.